Deep-Plane Approach to the Vertical Platysma Advancement: Technical Modifications and Nuances over 25 Years - Gordon, Neil A.; Sawan, Tareq G. (Facial Plastic Surgery, 2020)
In this article, we will provide the reader with the anatomical and embryologic evidence supporting the use of the deep-plane approach in rhytidectomy and insight into the evolution of the technique into the vertical platysma advancement. The original description of the deep-plane technique only described a basic superficial muscular aponeurotic system dissection in the midface with the ability to use tension on the flap without aesthetic consequences. This plane of dissection provides additional advantages not previously described, including access to deeper anatomical structures such as the buccal fat pad, and allows in vivo assessment and treatment of jowling. We describe how extension of this dissection and selective release of facial ligaments allows us to optimize treatment outcomes and longevity, especially in cases of difficult anatomy or revisions. Further advancements include case-specific facial volume enhancement, created by complex flap design, and facial narrowing by preauricular contouring and parotid hypertrophy treatment. Insights into anatomical landmarks, technical nuances, and alternative approaches for facial variations are presented.
Keywords: deep plane; facelift; rhytidectomy; midface; facial aging; aging neck; vertical platysma advancement; aesthetic surgery